Especialidades Tradicionales Garantizadas Made in Perú y la Propiedad Industrial como aliado en la reactivación del sector gastronómico - Manzur Filomeno, Karin Paola (2025)
In November 2021, DS 170-2021-PCM was enacted in Peru, approving the Regulations of the Protection Regime for Traditional Specialties Guaranteed and the Geographical Indications Regime. By May 2023, the Directorate of Distinctive Signs (DDS) of Indecopi granted the registration of the first Traditional Specialty Guaranteed (TSG) in Peru, and the second in Latin America: El Pan de Anís de Concepción. During the first quarter of 2024, the Traditional Specialty Guaranteed seal was published on the Peruvian State’s single digital platform. As can be seen, TSGs are a new legal figure in Peruvian Industrial Property legislation. The purpose of this article is to present, in an educational way, the relevant information that allows to know, with the necessary detail, the most notable aspects of the applicable legal framework. It also highlights the great potential they must contribute to strengthening the national gastronomic market.